SISTEM PENANDAAN TOKOH GANA PADA CANDI BUDDHA DI JAWA TENGAH (Faculty of Social Science, Universitas Negeri Semarang, 2009)
Temple as a Â result of culture during Hindu-Buddha Â is a building depicting cosmogony concept.Â Despitefully, temple also is Â a replica from mount Mahameru residence of the deities. Figure Gana isÂ one of creature chiseled at temple wall, as complement of depiction of cosmos. Existence of this fgureÂ at temple contains purposes and objectives. Problem which will be broken, that is: ( 1) How denotingÂ system of fgure Gana at Â temple Borobudur and Â temple Mendut? ( 2) How Â location denoting systemÂ of fgure Gana at the temple? This research is focused on the Gana at Borobudur and Mendut temples.Â The fgure of Gana is analysed by semiotic approach because by this approach every fgure chiseled atÂ temple relating to signs: signifer (â€˜penandaâ€™) and signifed (â€˜petandaâ€™), as according to semiotics studyÂ coverage. Semiotic analyse to Gana fgure can only be done if various descriptions about its ommissionÂ have been known. The informations which explain the Gana fgure have gotten from written sources ofÂ establishment rules and of symbolic meaning on every part of temple made by the architects and priestÂ alive in theirs days. The research procedure was divided into three phases: preparation, feld study, andÂ data analysis phase. From the result of this research and the discussion, we know that the depiction ofÂ Gana fgure at Borobudur and Mendut temples doesnâ€™t get out from cosmogony concept. Depiction systemÂ of Gana fgure was adapted by symbolic meaning on every parts of temple. So, it can be said that GanaÂ is an icon from a religious situation during Hindu-budha and a symbol from â€œupper worldâ€ (heaven).Â The location of Gana fgure at temple is becaming an icon from cosmogony concept.Keywords: Gana, temple, semiotic.